THE USE OF SMARTPHONE TECHNOLOGY AS AN INNOVATIVE LEARNING STRATEGY TO IMPROVE CONCEPT UNDERSTANDING AND PROBLEM SOLVING - Ihsan, Ahmad; Azizah, Latifatul; Haliza, Dwi Aprilia; Wahyuni, Tri; Puspitasari, Yesi (Journal on Research and Review of Educational Innovation, 2025)
Innovative learning strategies can be defined as approaches that encourage students to apply learning materials to themselves using a variety of engaging and interactive methods and media. The development of digital technology provides significant opportunities to enhance innovative learning methods, thereby helping students better understand concepts and improve their problem-solving skills. Learning motivation is crucial for students in schools because it influences their learning outcomes. The purpose of this article is to discuss innovative learning strategies that can enhance student learning motivation. This article was written using a literature review method by collecting data or sources related to the topic being discussed in the research. The result of this paper is a discussion of innovative learning strategies that can enhance student learning motivation. This study highlights the importance of learning motivation in influencing student learning outcomes and demonstrates that innovative methods such as flipped learning, blended learning, and e-learning can improve the quality of education.